2020
DOI: 10.14202/vetworld.2020.2502-2507
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and diversity of trypanosomes in sheep and goats from Mongo County in South Gabon, Central Africa

Abstract: Background and Aim: Trypanosomosis is a major impediment to livestock farming in sub-Saharan Africa. It is a vector-borne disease caused by several species of protozoan parasites, namely, trypanosomes. The present study aimed to identify the diversity of trypanosome species infecting sheep and goats from Mongo County and to determine the frequency of these parasites. Materials and Methods: This study was conducted on 286 trypanotolerant goats and sheep from Mongo regions located in South Gabon, using polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…Filter paper, however, inhibits ITS-PCR, making it less accurate compared to when DNA is extracted directly from whole blood samples (Ahmed et al, 2013). The frequency in trypanosome species, T. congolense and T. vivax distribution were similar with other findings (Kebede et al, 2009;Von Wissmann et al, 2011;Maganga et al, 2020), where goats were found to be highly prevalent in T. vivax as compared to cattle which is highly prevalent in T. congolense (Hassan-Kadle et al, 2020;Mulenga et al, 2021). In livestock, T. congolense and T. vivax are the most prevalent under natural infections, while T. brucei is the least prevalent (Van den Bossche and Delespaux, 2011;Maganga et al, 2020).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Filter paper, however, inhibits ITS-PCR, making it less accurate compared to when DNA is extracted directly from whole blood samples (Ahmed et al, 2013). The frequency in trypanosome species, T. congolense and T. vivax distribution were similar with other findings (Kebede et al, 2009;Von Wissmann et al, 2011;Maganga et al, 2020), where goats were found to be highly prevalent in T. vivax as compared to cattle which is highly prevalent in T. congolense (Hassan-Kadle et al, 2020;Mulenga et al, 2021). In livestock, T. congolense and T. vivax are the most prevalent under natural infections, while T. brucei is the least prevalent (Van den Bossche and Delespaux, 2011;Maganga et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…The frequency in trypanosome species, T. congolense and T. vivax distribution were similar with other findings (Kebede et al, 2009;Von Wissmann et al, 2011;Maganga et al, 2020), where goats were found to be highly prevalent in T. vivax as compared to cattle which is highly prevalent in T. congolense (Hassan-Kadle et al, 2020;Mulenga et al, 2021). In livestock, T. congolense and T. vivax are the most prevalent under natural infections, while T. brucei is the least prevalent (Van den Bossche and Delespaux, 2011;Maganga et al, 2020). The frequency of trypanosomes in goats indicates that goats are important reservoirs of trypanosomes that causes AAT and should be considered when undertaking AAT treatment control programmes in livestock.…”
Section: Resultssupporting
confidence: 91%
“…T. simiae is part of the Nannomonas subgenus as is T. congolense and it is the only trypanosome species that is particularly harmful to pigs, causing hyperacute, lethal infection with death occurring within 2 days after the onset of symptoms ( 47 ). The parasite can also be found in other domestic animals ( 48 ), therefore all livestock on the farm should be treated prophylactically. The pathogenicity of trypanosome infections varies greatly based on a variety of factors, including parasite characteristics (species and virulence), host characteristics (species, breed, age, immunological status, nutritional status, presence of co-infection, and physical condition), vector characteristics (species, density, infection rate, and host preference), epidemiological situation (endemic or epidemic), and the environment (e.g., the availability of food and water and the season) ( 3 ).…”
Section: The Trypanosoma Pathogenmentioning
confidence: 99%
“…This species has been previously reported in livestock in Cameroon, especially in cattle from Adamawa and North regions [ 8 , 11 , 12 , 33 ]. The occurrence of T. theileri has also been detected in small ruminants, both goats and sheep, in neighbouring Gabon [ 81 ].…”
Section: Discussionmentioning
confidence: 99%